Can a construction boom create new sources of power for trade unions? a case study of the 2010 World Cup and its impact on the construction industry - Chinguno, Crispen (My University, 2009)
Abstract There is general consensus that the reorganisation of production and labour processes have resulted in the diminishing of a collective voice at most workplaces. However, there is contested debate on the possibility of a revitalisation of a labour movement whose structural power has been extensively undermined. This study examines potential for the establishment of new sources of power that may compensate for the weak trade union structural power. The study uses the South Africa 2010 construction boom as a case study to explore the question. It adopts a qualitative research approach using interviews, participant observation and document analysis. The study affirms earlier studies that suggested potential of new sources of power and strategies to sustain associational and symbolic power which may compensate for weak structural power. However, the study noted a lack of consciousness or reluctance on the part of the trade unions in adopting the new strategies. They instead ironically alienate self from the workers who constitute the majority. The study suggests that workers have potential to make use of both the old and new sources of power outside the trade unions but in other collective forms which may be informal. The use of this power is not only confined to workplace struggles but can be used in other struggles outside the workplace. The potential of the new sources of power cannot however, be fully realised as long as the trade unions are oblivious of the workers who constitute the majority of the workforce.